PENGARUH PENERAPAN GOOD GOVERNMENT GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Kasus pada Pemerintah Daerah di Provinsi Jawa Barat dan Banten) - Septi Masitoh, Dewi Sarifah Tullah, Erma Apriyanti (Jurnal Ekonomi STIEP, 2020)
This study aims to determine the effect of Good Government Governance and human resource competencies,on the quality of regional financial reports. The population in this study were all district / city governments inthe provinces of Java and Banten. The sampling technique used is the census method. The data used areprimary data, namely giving questionnaires totaling 3 sets aimed at the Head of Office and the Head ofAccounting in the local governments of Java and Banten Provinces. The Head of Service fills in thequestionnaire about Good Government Governance and the quality of the report, while the Head of Accountingfills in about human resource competencies. The data analysis method used is multiple linear regressionanalysis. The results of this study prove that Good Government Governance has a positive effect on the qualityof regional financial reports in the Provinces of West Java and Banten, while human resource competencedoes not affect the quality of regional financial reports in the Provinces of West Java and Banten